Specific Intervention to Prevent Stunting Through Iron Supplementation in Adolescent Girls in Jambi City - Siregar, Sri Astuti; Asparian, Asparian; Lanita, Usi (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Adolescent girls are a vulnerable group that needs special attention in efforts to prevent stunting, considering their important role in shaping the future generation. Based on RI Presidential Decree No. 72 of 2021 concerning the acceleration of stunting reduction, specific interventions are activities carried out to address the direct causes of stunting, where one of the interventions is blood supplementation tablets for adolescent girls. Objective: This study aims to determine how specific interventions for preventing stunting through iron supplementation for adolescent girls in Jambi City. Method: This research uses quantitative methods with a cross-sectional approach where the sample is all teenagers Woman in Jambi City Public High School as many as 105 people using proportional simple random sampling technique. Result and Discussion: The results of the analysis show that the teacher and parent support variable have a significant effect on the implementation of  the blood supplementation tablet program. Conclusions: Consumption behavior variables, anemia status and perception did not have a significant effect. The variables teacher support and parental support have a significant  effect on the implementation of the iron supplementation program. Expected from teenagers woman to continue  consuming iron regularly and the school to be able to implement a regular iron supplementation program in full coordination with the Community Health Center.